2009
DOI: 10.1080/00036840701320241
|View full text |Cite
|
Sign up to set email alerts
|

Do part-time/full-time compensation differentials for nurses vary between the private and public sector?

Abstract: This study examines whether, compared to their private sector counterparts, public sector health care employers are at a disadvantage using part-time (PT) nurses to lower labour costs. Findings reveal a lack of a PT wage differential. Public and Private sector PT nurses are less likely to receive health care and pension coverage compared with full-time (FT) nurses. Yet, these PT/FT nonwage compensation coverage differentials do not vary across sectors. The nonwage findings are interpreted as suggesting that pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…One reason that PCNPs may not work in primary care settings is that they earn lower wages working in primary care than in specialty care settings (Bodenheimer & Bauer, 2016;Coomer, 2013;Jones & Gates, 2004;McGregory, Niederjohn, & Peoples, 2009;Petterson, Phillips, Bazemore, Burke, & Koinis, 2013;Schumacher & Hirsch, 1997;Walani, 2013). For NPs, Goolsby (2006) used the 2004 data file of the National Nurse Practitioner Sample Survey (NNPSS) conducted by the American Academy of Nurse Practitioners and reported that, regardless of certification, the average hourly wage of NPs working in primary care settings was $36.51, considerably lower than the $39.59 average wage for those working in specialty care settings.…”
Section: Introductionmentioning
confidence: 99%
“…One reason that PCNPs may not work in primary care settings is that they earn lower wages working in primary care than in specialty care settings (Bodenheimer & Bauer, 2016;Coomer, 2013;Jones & Gates, 2004;McGregory, Niederjohn, & Peoples, 2009;Petterson, Phillips, Bazemore, Burke, & Koinis, 2013;Schumacher & Hirsch, 1997;Walani, 2013). For NPs, Goolsby (2006) used the 2004 data file of the National Nurse Practitioner Sample Survey (NNPSS) conducted by the American Academy of Nurse Practitioners and reported that, regardless of certification, the average hourly wage of NPs working in primary care settings was $36.51, considerably lower than the $39.59 average wage for those working in specialty care settings.…”
Section: Introductionmentioning
confidence: 99%